2012
DOI: 10.1248/bpb.b12-00623
|View full text |Cite
|
Sign up to set email alerts
|

Diarylheptanoids from <i>Alnus japonica</i> Inhibit Papain-Like Protease of Severe Acute Respiratory Syndrome Coronavirus

Abstract: The papain-like protease (PL pro ), which controls replication of the severe acute respiratory syndrome coronavirus (SARS-CoV), has been identified as a potential drug target for the treatment of SARS. An intensive hunt for effective anti-SARS drugs has been undertaken by screening for natural product inhibitors that target SARS-CoV PL pro . In this study, diarylheptanoids 1-9 were isolated from Alnus japonica, and the inhibitory activities of these compounds against PL pro were determined. Of the isolated dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
133
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 165 publications
(137 citation statements)
references
References 24 publications
0
133
0
1
Order By: Relevance
“…[12, 13] Fragments F1 – F8 were repurchased from Sigma. Compound purity has been determined by NMR to be ≥95%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[12, 13] Fragments F1 – F8 were repurchased from Sigma. Compound purity has been determined by NMR to be ≥95%.…”
Section: Methodsmentioning
confidence: 99%
“…[12] Second, several natural products, diarylheptanoids isolated from Alnus Japonica , showed inhibitory activity (4.1 µM IC 50 ) against PLpro. [13] In addition to its primary function of viral peptide cleavage, PLpro has been recognized to be involved in deubiquitination, de-ISGylation, and viral evasion of the innate immune response. [2a, 14] SARS-PLpro is a cysteine protease that contains a zinc-binding motif, a catalytic triad, and an ubiquitin-like N-terminal domain (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…[40][41][42][43][44][45] However,a few low-nm-range inhibitors have been identified that can be used in combination with other protease-inhibitor therapies to help combat the virus. Many of the inhibitors are in the micromolar range in terms of binding to and inhibiting the two proteases.…”
Section: Rna-dependent Rna Polymerasementioning
confidence: 99%
“…In a FRET-baseda ctivity assay,t he IC 50 value of GC376a gainst recombinant SARS 3CLpro was found to be 4.9 times that against FIPV 3CLpro( 4.35 vs. 0.72 mm,r espectively). Arepresentation of the top CoV protease inhibitors providing ascaffold to perform SAR studies in termsofdesigning novel small-molecule protease inhibitors for 2019-nCoV [40][41][42][43][44][45]49] .3 CLpro-1, the most potent inhibitor,ish ighlighted. Figure 7.…”
Section: Rna-dependent Rna Polymerasementioning
confidence: 99%
“…Diarylheptanoids exhibited antiviral activities against influenza virus [61][62][63][64][65], RSV [44,66], poliovirus [44], measles virus [44], herpes simplex virus type 1 (HSV-1) [44], human immunodeficiency virus (HIV) [67], severe acute respiratory syndrome (SARS) virus [68], and Epstein-Barr virus in relation to carcinogenesis [69]. They are characterized as compounds possessing broad antiviral spectrum against DNA and RNA viruses.…”
Section: Antiviral Activities Of Diarylheptanoidsmentioning
confidence: 99%